2015
DOI: 10.1176/appi.ajp.2014.14030313
|View full text |Cite
|
Sign up to set email alerts
|

COMT Haplotypes Modulate Associations of Antenatal Maternal Anxiety and Neonatal Cortical Morphology

Abstract: These results suggest that the association between maternal anxiety and in utero neurodevelopment is modified through complex genetic variation in COMT. Such genetic moderation may explain, in part, the variation in phenotypic outcomes in offspring associated with maternal emotional well-being.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
88
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(91 citation statements)
references
References 72 publications
3
88
0
Order By: Relevance
“…Relevant to the current study is evidence that the well-documented association between prenatal maternal anxiety or stress and child outcome cited above may be moderated by the child’s COMT genotype [16]. A report from Singapore on 146 neonates indicated that the association between prenatal maternal anxiety and neonatal cortical morphometry was moderated by genetic variation in COMT [16], with increased thickness of the ventrolateral prefrontal cortex observed in neonates with the val allele.…”
Section: Introductionmentioning
confidence: 65%
“…Relevant to the current study is evidence that the well-documented association between prenatal maternal anxiety or stress and child outcome cited above may be moderated by the child’s COMT genotype [16]. A report from Singapore on 146 neonates indicated that the association between prenatal maternal anxiety and neonatal cortical morphometry was moderated by genetic variation in COMT [16], with increased thickness of the ventrolateral prefrontal cortex observed in neonates with the val allele.…”
Section: Introductionmentioning
confidence: 65%
“…This was demonstrated in a study of the effects of antenatal maternal anxiety and infant COMT genotypes (Val158Met, rs737865 and rs165599) on neonatal cortical thickness 159 . Neither maternal anxiety nor infant COMT genotype were related to regional cortical thickness individually; however, interaction effects between maternal anxiety and infant genotype were observed in several regions, including the right ventromedial prefrontal cortex, an area involved in the regulation of anxiety and mood.…”
Section: Influences Of Genes and Environmentmentioning
confidence: 86%
“…For instance, prenatal anxiety was reported to associate with offsprings' gray matter volume reductions in the prefrontal cortex at 6-9 years of age (Buss et al, 2010). A separate study similarly observed an effect of prenatal maternal anxiety on neonatal frontal cortical thickness that was moderated by functional variants of the catechol-O-methyltransferase (COMT) gene, which regulates catecholamine signaling and is implicated in anxiety, pain, and stress responsivity (Qiu et al, 2014). Furthermore, a strong positive association was observed between postnatal maternal anxiety and offspring right hippocampal growth and a strong negative association between postnatal maternal anxiety and offspring left hippocampal volume at 6 months of age (Pruessner et al, 2008;Qiu et al, 2013).…”
Section: Neuroanatomicalmentioning
confidence: 98%